2016
DOI: 10.1016/j.addbeh.2016.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Social support as a buffer between discrimination and cigarette use in juvenile offenders

Abstract: Cigarette use is a prominent problem in juvenile offenders, leading to negative health outcomes and substance use. One interesting precipitator of cigarette use in this population is discrimination. Social support could potentially buffer the positive relationship between cigarette use and discrimination in juvenile offenders, which could be dependent on the context in which the discrimination is experienced, such as peer, institutional (e.g., stores, restaurants), or educational contexts. The present study ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…From the perspective of the victim of discrimination, it may not be possible to distinguish clear lines between parts of their identity for the sole reason for the experience of discrimination. Our attempt to address this concern was to combine the forms of discrimination because discrimination in any form can negatively influence well‐being (Hershberger, Zapolski, & Aalsma, ).…”
Section: Discussionmentioning
confidence: 99%
“…From the perspective of the victim of discrimination, it may not be possible to distinguish clear lines between parts of their identity for the sole reason for the experience of discrimination. Our attempt to address this concern was to combine the forms of discrimination because discrimination in any form can negatively influence well‐being (Hershberger, Zapolski, & Aalsma, ).…”
Section: Discussionmentioning
confidence: 99%
“…Findings from U.S. studies are inconsistent on whether social support buffers the effects of ethnic discrimination on health [21, 25, 36, 37]. Further, only one of these studies examined smoking-related outcomes and found that at low levels of social support, youth who experienced greater educational discrimination had higher levels of nicotine addiction severity than youth with high levels of social support [26]. Indeed, research on discrimination suggests that seeking social support is a commonly used coping strategy following interpersonal discriminatory events [38–40].…”
Section: Discussionmentioning
confidence: 99%
“…It can also guide individuals in using effective coping strategies to respond to discrimination [23]. Though the stress process model is widely used in health research, specific concepts, such as the buffering effects of social support, have received less empirical examination [21, 2426]. In this study, we investigate the effect of two forms of ethnic discrimination against Arabs, interpersonal and perceived institutional group discrimination, on smoking outcomes and whether social support buffers those effects.…”
Section: Introductionmentioning
confidence: 99%
“…Smoking poses a risk for both health and substance abuse (34). It has been suggested that smoking in juveniles draged to crime is associated with an inadequate social support (35).…”
Section: Discussionmentioning
confidence: 99%